A QUALITATIVE SOCIOLOGICAL STUDY OF ETHNO-TOLERANT MENTALITY OF THE NEVA REGION POPULATION - E. A. Okladnikova (Дискурс)
The article discusses the production process of ethno-tolerant mentality reflected in the narratives of contemporary aboriginal population of St. Petersburg and the Leningrad region, i.e. the territory of the Neva region. (Prinevsky region) The main provisions of the article are based on the results of the pilot sociological research of 2015, conducted using a narrative interview in the territory of the Neva region. The purpose of the article is justification of the idea of dependence on information institutionalization of urban and rural residents of the Leningrad region, on the depth of their historical memory, the degree of social and cultural nostalgia, of their level of knowledge about the archaic roots of the indigenous culture of the Prinevsky region. The analysis of respondents’ answers to the questions of the research guide allowed to make conclusions that information institutionalization is the basic factor of production tolerant mentality.